If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4(1 + -2x) = 2x + -1(x + 1) 3x + (1 * -4 + -2x * -4) = 2x + -1(x + 1) 3x + (-4 + 8x) = 2x + -1(x + 1) Reorder the terms: -4 + 3x + 8x = 2x + -1(x + 1) Combine like terms: 3x + 8x = 11x -4 + 11x = 2x + -1(x + 1) Reorder the terms: -4 + 11x = 2x + -1(1 + x) -4 + 11x = 2x + (1 * -1 + x * -1) -4 + 11x = 2x + (-1 + -1x) Reorder the terms: -4 + 11x = -1 + 2x + -1x Combine like terms: 2x + -1x = 1x -4 + 11x = -1 + 1x Solving -4 + 11x = -1 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + 11x + -1x = -1 + 1x + -1x Combine like terms: 11x + -1x = 10x -4 + 10x = -1 + 1x + -1x Combine like terms: 1x + -1x = 0 -4 + 10x = -1 + 0 -4 + 10x = -1 Add '4' to each side of the equation. -4 + 4 + 10x = -1 + 4 Combine like terms: -4 + 4 = 0 0 + 10x = -1 + 4 10x = -1 + 4 Combine like terms: -1 + 4 = 3 10x = 3 Divide each side by '10'. x = 0.3 Simplifying x = 0.3
| 2(a-b)= | | 3.7(-83x+-3)=3.7(7x+-30) | | (2x-1/2)^2=9/4 | | X+2x+4x+2=37 | | (13-6)x(12-3)+16= | | 3a^2+25+42=0 | | 9n=6 | | -49=.7y | | 2[5(4-1)]= | | x-4=169 | | t^2-19t+10=0 | | x^2y^2-2y=0 | | in(2x)-in(3x+2)=1 | | -8(w-3)=9w+41 | | (7x-9)(9x+9)=0 | | (49-12)/3 | | (2x-7)(9x+8)=0 | | 17=85 | | 17Xa=85 | | x+25=51 | | 3p^3+12p=0 | | 4(p+17.00)=53.50 | | 4p+17.00=53.00 | | 4p-17.0=53.00 | | 0.1x=0.35 | | 9x-2y/3*5z | | 0.35x=0.1 | | -8y-10xy= | | 0.1x-0.01x=1 | | -5b-b= | | -2x^2+3x^2= | | -2x^2-3x^2= |